2005
DOI: 10.1677/jme.1.01601
|View full text |Cite
|
Sign up to set email alerts
|

Gene regulation by NMDA receptor activation in the SDN-POA neurons of male rats during sexual development

Abstract: The present study was designed to identify possible signaling pathways, which may play a role in prevention of neuronal apoptosis in the sexually dimorphic nucleus of the preoptic area (SDN-POA) after physiological activation of the N-methyl-D-aspartate (NMDA) receptor. Gene response to the blockage of the NMDA receptor by an antagonist (dizocilpine hydrogen maleate; MK-801) was screened after suppression subtractive hybridization (SSH). The results showed that dfferential screening after SSH detected the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…For example, bcl-2 (an anti-apoptotic protein) expression is higher in male than female rats on postnatal day 8, consistent with the overall larger POA size of male rats [78]. A subsequent study from the Hsu group also showed specificity of this phenomenon to the SDN-POA, for which bcl-2 expression was higher in neonatal (postnatal day 2) males than females [79]. Davis et al found that the number of apoptotic cells in the SDN-POA exhibited differential developmental profiles between the sexes, peaking at postnatal day 6 in males and later (between days 7-10) in the females [40].…”
Section: Mechanisms For Hormone Effects On Avpv and Sdn-poa Morphologymentioning
confidence: 61%
“…For example, bcl-2 (an anti-apoptotic protein) expression is higher in male than female rats on postnatal day 8, consistent with the overall larger POA size of male rats [78]. A subsequent study from the Hsu group also showed specificity of this phenomenon to the SDN-POA, for which bcl-2 expression was higher in neonatal (postnatal day 2) males than females [79]. Davis et al found that the number of apoptotic cells in the SDN-POA exhibited differential developmental profiles between the sexes, peaking at postnatal day 6 in males and later (between days 7-10) in the females [40].…”
Section: Mechanisms For Hormone Effects On Avpv and Sdn-poa Morphologymentioning
confidence: 61%
“…Previously, we have demonstrated that the apoptotic incidence of neurons in SDN-POA of male rats is significantly increased when NMDA receptor is blocked by MK-801 (Hsu et al 2001) and the physiological activation of NMDA receptor may protect against neuronal death by transcriptional increase of some survival-related genes, including COII, in SDN-POA during sexual development (Hsu et al 2005). In this study, we attempted to map the signaling pathway of NMDA receptor-mediated neuronal survival in the GT1-7 cell lines, which were derived from hypothalamic GnRH neurons and expressed NMDA receptor as well as mitochondrial COII genes, by comparing the time course of intracellular events, which have been suggested to be involved in the neuronal apoptosis, induced by blocking the activation of NMDA receptor.…”
Section: Discussionmentioning
confidence: 98%
“…The apoptotic incidence of neurons in the sexually dimorphic nucleus of the preoptic area (SDN-POA) of male rats is significantly increased when the NMDA receptor is blocked by MK-801 (Hsu et al 2001). Recently, we reported that some neurotropic genes (RNA binding motif protein 3 (RBM3), cytosolic phosphoprotein (P19), cytoskeletal gactin, and a-tubulin) as well as survival-related genes (Bcl-2, cytochrome oxidase subunits II, III (COII), (COIII), and cytochrome b) in SDN-POA of neonatal male rats were significantly down-regulated when the NMDA receptor was blocked (Hsu et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Cugbp2 regulates splicing, stabilization or translation of NMDA receptor subunit 1 (Nr1) (Dembowski and Grabowski, 2009), cyclooxygenase 2 (Cox2) (Mukhopadhyay et al, 2003a;Ramalingam et al, 2012) and AR (Miyazaki et al, 2012a). These mRNAs have been previously linked to sexual differentiation of the POA (Hsu et al, 2001(Hsu et al, , 2005McCarthy, 2002, 2004;Zuloaga et al, 2008). Therefore, we performed follow-up studies on Cugbp2 mRNA.…”
Section: Identification Of Sex-dependent and E 2 -Regulated Genes In mentioning
confidence: 99%
“…NMDA R1 splice variants produce NMDA receptors with different characteristics (Durand et al, 1993;Tingley et al, 1993). Although not studied in the AVPV, post-transcriptional (Hsu et al, 2001(Hsu et al, , 2005 regulation of Nr1 appears to mediate protective effects of E 2 in the developing SDN-POA (Hsu et al, 2001). Interestingly, a-actinin two, a protein that directly anchors NMDA receptors in the post-synaptic density (Wyszynski et al, 1997(Wyszynski et al, , 1998, was also upregulated in the male and Cugbp2 regulates splicing of a-actinin (Gromak et al, 2003).…”
Section: à15mentioning
confidence: 99%